engaruh Rasio Keuangan dan Agency Cost untuk Memprediksi Kondisi Financial Distress - Devi Amelia; Rianti Setyawasih (Fakultas Ekonomi Universitas Islam 45, 2020)
Financial distress is a decline in the company's financial condition that occurred before bankruptcy. This research was conducted to examine the effect of profitability, liquidity, activity leverage and agency cost on financial distress. This research was conducted at retail companies listed on the Indonesia Stock Exchange in 2016-2019. The sample used in this study were 14 companies selected using purposive sampling. The analysis technique used is logistic regression analysis. The results of the analysis of this study state that liquidity and leverage have a positive effect on financial distress, activity has a negative effect on financial distress, profitability and agency costs have no effect on financial distress.Keywords: profitability; liquidity; leverag; activity; agency cos; financial distress.